Environmental Impacts of Green Open Space in Urban Indonesia: A Difference-in-Differences Analysis - ILMIAWAN AUWALIN; RUMAYYA; NI MADE SUKARTINI (Asian Development Review)
This study investigates the impact of green open spaces in reducing the probability of flooding and open waste burning in urban areas in Indonesia’s three largest metropolitan cities: Surabaya, Jakarta, and Medan. This study employs urban village microdata from the 2014 and 2018 Village Potential Census. First, we construct the dataset into a difference-in-differences setup. The urban villages that initially did not have any green open spaces in 2014 and then had them in 2018 were assigned as the treatment group, and those without any green open spaces in both periods were the comparison group. Then, we estimated the impact of urban green spaces on the probability of flooding and open waste burning. The results indicate that the likelihood of flooding and open waste burning had decreased in treated areas by 2018.